DIE PROBLEMATIEK VAN MILITÊRE OPLEIDING - Heydenrych, M.H (Scientia Militaria - South African Journal of Military Studies, 2012)
"The essential characteristics of a good army are that it be well trained and well disciplined. These two characteristics are apparent in ever unit achievement, whether in peace or in war. Discipline derives and flows from training and serves to emphasize a fundamental point essential to a philosophy of training: that training is all encompassing. Training permeates everything a military organization does" (Collins 1978: 1).